Myocardial Expression of Estrogen Receptor-mRNA Is Associated With Lower Markers of Post-operative Organ Damage in Young Patients With Congenital Cardiac Defect - Rouatbi, Hatem; Farhat, Nesrine; Heying, Ruth; Vazquez-Jimenez, Jaime F.; Parent, Anne-Simone; Seghaye, Marie-Christine (Frontiers in Pediatrics, 2021)
Background Estrogen receptors (ERs) relate to cardio-protection in adults but their role in younger patients is not known. We aimed to assess myocardial expression of ER- and ER- mRNA in young patients with congenital cardiac disease and to analyse their putative protective role. Patients and methods 20 children and young adults (7 females, 13 males) with a median age of 13.8 years (interquartile range [IQR]: 12.3 years) were enrolled in this prospective study. Myocardial expression of ER-mRNA and genes involved in inflammation, growth and stress response was assessed by real time PCR and was correlated to post-operative (po) outcome. Results ER-mRNA was detected in the myocardium of all patients, independently of gender and age. Expression of ER-mRNA correlated with that of mRNA coding for BNP and for all cytokines tested. Higher ER-mRNA expression correlated with lower troponin T concentrations 24 hours po (p=0.032), higher PaO2/FiO2 ratio 4 hours po (p= 0.059) lower fluid retention 4 hours po (p=0.048), and lower AST levels 24 hours po (p=0.047). Also higher ER-mRNA expression was correlated with lower fluid retention 24 hours po (p=0.048). Patients in whom levels of ER- and ER-mRNA were > P50 had lower troponin T- (p=0.003, respectively) and lower AST concentrations 24 hours po (p=0.043, respectively) than the others. Conclusions Expression of ER and ER-mRNA is present in the myocardium of children and young adults with congenital cardiac defect and is associated with lower markers of po organ damage.This suggests that ERs may provide perioperative organ protection in this population.